KERJASAMA PERTAHANAN TIONGKOK DAN INDONESIA STUDI KASUS NAVY TO NAVY TALK PERIODESASI 2015-2018 - Silalahi, Pelita (2019)
Defense cooperation between Indonesia and Tiongkok has been established since 2005 is renewed in 2015 namely Joint statement on strength comprehensive strategic partnership between the people's republic of China and the Republic of Indonesia. Navy To Navy Talk as a forum is an interesting research for understanding the implementation of defense cooperation. Researcher want to comprehend the implementation of such cooperation between both naval coutries within the last three years. Researcher will use descriptive method to obtain better insight regarding the naval coooperation between Indonesia and Tiongkok in Neoliberal Institusional inside the framework of cooperation and also concepts defense policy both Indonesia and Tiongkok , defense diplomacy as negotiating interestests and defense cooperation of navy talk in implementation . From the results of the research, the researchers acquire implementation of Navy To Navy Talk in 2015-2018 had lot of contribute in defense field. From such dialog forum, both countries can strengther each defense field to view the dynamic of their strategic enviroment. Researcher figures out that both countries favor any cooperation in military education most easily accepted by both countries as specialy Indonesia to realizing maritime fulcrum